STUDI LITERATUR KEANEKARAGAMAN JENIS BURUNG DI BERBAGAI PULAU DI KEPULAUAN SERIBU, DKI JAKARTA - Syahrurromadhan, Gempa Fi; Awaliyah, Nadia N; Putri, Tiara A; Mufidah, Nailam R; Hidaya, Nurul; Rusdi, Rusdi; Sartono, Nurmasari (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: The Thousand Islands is a collection of islands that support the life of various types of birds. The islands in the Thousand Islands are inhabited by a variety of birds, especially waterbirds and shorebirds. Methods: Data were obtained through literature study from research articles. Results: The results of the literature show that Pramuka Island has a bird diversity index of 2.4334 and is the highest value among other islands in the Thousand Islands. Conclusion: Several islands in the Thousand Islands, which include Rambut Island, Pramuka Island, Opak Besar Island, Bulat Island, Genteng Besar Island, Putri Barat Island, Bintang Island, Kaliage Island, Kotok Island, Harapan Island, and Melintang Besar Island. has a diversity that is included in the medium category. The highest bird diversity is found on Pramuka Island (H' = 2.4334), but the highest balance is found on Pamegaran Island (E = 0.8007) which is quite wide and undisturbed.